Profile Quantitative Hepatitis B Surface Antigen (qHBsAg) of Chronic Nai?ve Hepatitis B Patients in Dr. Soetomo Hospital, Surabaya, Indonesia - Yessy Puspitasari; Puspa Wardhani; Munawaroh Fitriyah; Erik Hasudungan; Atika; Ummi Maimunah; Aryati (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to evaluate the profile of qHBs Ag profile, and also to investigate the correlation betweenqHBs Ag and HBV DNA. Seventy samples of chronic-nai?ve hepatitis B patients in Dr. Soetomo Hospitalwere analyzed in a cross-sectional study. Patients were categorized according to the HBe Ag positive (n=30)and HBe Ag negative (n=18), also based on qHBs Ag 1000 IU/mL and qHBs Ag >1000 IU/mL. qHBs Agwas correlated with HBV DNA. qHBs Ag by CLEIA method from Sysmex, KOBE HISCL, HBV DNAwas measured by real-time Polymerase Chain method from Gene Xpert, Cepheid. 70 patients nai?ve CHBtreatment showed a median of ALT level 60.21±70.76 U/L. 30 patients showed a positive-HBeAg, 18 patientsshowed negative-HBeAg, 22 patients were not evaluated (N/A). Positive-HBeAg patients had 70% qHBsAg>2500 mg/dL and median HBV DNA 7.49×107IU/mL. Negative-HBeAg patients had 55.6% HBsAg ?1000mg/dL and median HBV DNA 9.66×102 IU/mL. qHBsAg correlated with HBV DNA (p <0.001). This datademonstrated that quantitative HBsAg was associated with a phase of HBV-infection, quantitative HBsAgshowed a moderate correlation with DNA HBV, quantitative HBsAg levels might be a predictor of initiationtherapy for CHB patients.